DEVELOPMENT OF TEACHING MATERIALS USINGREALISTIC MATHEMATICS EDUCATION APPROACHES IN IMPROVING THE CAPACITY OF MATHEMATIC COMMUNICATION OF PGSD STUDENTS - Sukma Murni; Siti Ruqoyyah; Sylvia Rabbani (Institut Pendidikan Tapanuli Selatan, 2021)
This research is motivated by the lack of mathematical communication skills of PGSD IKIP Siliwangi students. The purpose of this study is to improve the mathematical communication skills of PGSD IKIP Siliwangi students through the Realistic Mathematics Education (RME) approach with the help of teaching aids. The specific target to be achieved in this research is the formation of teaching materials that are appropriate, practical, efficient, and effective, and can also develop the productivity of PGSD IKIP Siliwangi students. This research uses a quantitative approach and uses a quasi-experimental method. The population in this study was PGSD IKIP Siliwangi students, while the sample consisted of 70 students who were divided into 35 students in class A1 of 2017 as an experimental group and 35 students in class A2 in 2017 as a control group. The instrument used consisted of written tests regarding mathematical communication skills and the practice of making teaching aids, observations and interviews. The results showed that there was an increase in mathematical communication skills of PGSD students using the RME approach better than those using ordinary learning.